2010
DOI: 10.1002/jms.1794
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous HPLC‐DAD‐MS (ESI+) determination of structural and geometrical isomers of carotenoids in mature grapes

Abstract: Carotenoids are uniquely functional polyene pigments ubiquitous in nature; aside from being responsible for the color of a wide variety of vegetables, interest is being focused on food carotenoids due to their likely health benefits. From analytical point of view, it is important to unequivocally identify individual carotenoid compounds in many food stuffs. Therefore, isolation of standards from natural sources must be encouraged for accurate identifications. Like many fruits, mature grape berries contain nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 47 publications
2
53
3
Order By: Relevance
“…The lutein to ß-carotene ratio in grapes, are highly variable depending on the viticulture region and on the variety analyzed. In some varieties (Sauvignon, Pinot Noir and Merlot) some authors found that lutein level was almost double compared to ß-carotene while in other varieties the concentration of this two carotenoids are similar or even higher for ß-carotene [23]. …”
Section: Resultsmentioning
confidence: 99%
“…The lutein to ß-carotene ratio in grapes, are highly variable depending on the viticulture region and on the variety analyzed. In some varieties (Sauvignon, Pinot Noir and Merlot) some authors found that lutein level was almost double compared to ß-carotene while in other varieties the concentration of this two carotenoids are similar or even higher for ß-carotene [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Forty milligram of freeze-dried berry powder have been used for each extraction, and APCI-MS settings were as following: sheath and auxiliary gas, set to 30 and 12 units, respectively; the vaporizer temperature and the capillary temperature were set to 270 and 220°C, respectively, while the discharge current was set to 3.5 μA, and the capillary voltage and tube lens settings were 25 V and 80 V. Identification was performed using literature data (Mendes-Pinto et al, 2004; Crupi et al, 2010; Kamffer et al, 2010), and on the basis of the m/z accurate masses, as reported on Pubchem (http://pubchem.ncbi.nlm.nih.gov/) or Chemspider (http://www.chemspider.com). Linoleic and linolenic acids have been analyzed using the same experimental conditions, confirmed by using authentic standards, and have been relatively quantified as fold on the internal standard (α-tocopherol acetate) level.…”
Section: Methodsmentioning
confidence: 99%
“…From the obtained UV-vis spectra information it was possible to identify 26 compounds, corresponding 12 to carotenoids and the other to chlorophyll a and b and their deriva-tives. A tentative identification of the six main separated carotenoid compounds was accomplished by comparing the UV-vis and MS spectra information provided by the two detectors (i.e., DAD and MS) with commercial standards and data from the literature (Britton, Liaaen-Jensen, & Pfander, 2004;Castro-Puyana et al, 2013;Crupi, Milella, & Antonacci, 2010). Information about characteristic UV-Vis spectra, [M + H] + , and the main fragments obtained by MS 2 experiments for the different carotenoids is presented in Table 3, together with their quantification in the two sampling days.…”
Section: Carotenoid Profilementioning
confidence: 99%